The phenomenon of love in Russian cultural tradition - M V Moiseenko (RUDN Journal of Philosophy, 2014)
The article is devoted to the research of the particularity of the phenomena of love in Russian cultural tradition. This phenomena is studied through the prism of Russian folklore, Russian classic literature, romance, secular paintings of the age of Enlightenment and Orthodox art. In this research the author pays particular attention to the judgments of the Russian philosophers abroad: N.A. Berdiaev, I.A. Ilyin, G.P. Fedotov.